Priority Directions for Enhancing the Governance Efficiency of Educational Institutions - Sherzod Mukhamedov (Researchparks Publishing, 2026)
This article examines the priority areas for enhancing the governance efficiency of educational institutions in response to global transformations and the demands of the digital economy. The research explores a transition from traditional, rigid administrative monitoring toward an agile, strategic leadership model that maximizes human capital. Through a comprehensive systemic framework, the author details six foundational pillars of modern school administration: strategic leadership, data-driven management, instructional mentorship, financial sustainability, socio-emotional well-being, and digital transformation. The study highlights that integrating artificial intelligence and electronic management platforms mitigates bureaucracy, while anchoring executive decisions in empirical metrics (KPIs) ensures organizational proactivity. Furthermore, within the educational landscape of Uzbekistan, harmonizing these administrative dimensions elevates the institutional mission, transforming schools from mere service providers into innovative, high-performing intellectual hubs. Ultimately, the paper concludes that a leader's strategic vision, coupled with collective solidarity and localized mentorship, serves as the primary mechanism for a sustainable trajectory of academic advancement.